Water and lipid suppression techniques for advanced 1H MRS and MRSI of the human brain: Experts' consensus recommendations - Tkáč, Ivan; Deelchand, Dinesh; Dreher, Wolfgang; Hetherington, Hoby; Kreis, Roland; Kumaragamage, Chathura; Považan, Michal; Spielman, Daniel M.; Strasser, Bernhard; Graaf, Robin A. (NMR in biomedicine, 2021)
The neurochemical information provided by proton magnetic resonance spectroscopy (MRS) or MR spectroscopic imaging (MRSI) can be severely compromised if strong signals originating from brain water and extracranial lipids are not properly suppressed. The authors of this paper present an overview of advanced water/lipid‐suppression techniques and describe their advantages and disadvantages. Moreover, they provide recommendations for choosing the most appropriate techniques for proper use. Methods of water signal handling are primarily focused on the VAPOR technique and on MRS without water suppression (metabolite cycling). The section on lipid‐suppression methods in MRSI is divided into three parts. First, lipid‐suppression techniques that can be implemented on most clinical MR scanners (volume preselection, outer‐volume suppression, selective lipid suppression) are described. Second, lipid‐suppression techniques utilizing the combination of k‐space filtering, high spatial resolutions and lipid regularization are presented. Finally, three promising new lipid‐suppression techniques, which require special hardware (a multi‐channel transmit system for dynamic B1+ shimming, a dedicated second‐order gradient system or an outer volume crusher coil) are introduced. The neurochemical information provided by 1H MRS or MRSI data can be severely compromised if strong signals originating from the brain water and extracranial lipids are not properly suppressed. The authors of this paper present an overview of advanced water/lipid‐suppression techniques and describe their advantages and disadvantages. In addition, recommendations for choosing the most appropriate technique and for their proper usage are provided.